Porous Fe2O3-Mn2O3 core-shell cubic structure material for lithium ion battery and preparation method of porous Fe2O3-Mn2O3 core-shell cubic structure material
Through the preparation of porous Fe2O3@Mn2O3 core-shell cubic structure materials, the problems of low capacity, poor safety and poor rate performance of the anode material of lithium-ion batteries are solved, and lithium-ion with high capacity, safe working potential and good electrochemical performance are achieved Battery electrode materials meet the energy needs of the energy storage industry.
Patent Information
- Application Number
- CN202411786971.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Existing lithium-ion battery anode materials have problems such as low theoretical specific capacity, poor safety, poor rate performance and insufficient cycle stability. Especially commercial graphite anodes may lead to 'dead' lithium and lithium dendrites at operating potentials, resulting in capacity. Fast attenuation and reduced safety.
The porous Fe2O3@Mn2O3 core-shell cubic structure material is prepared by one-step hydrothermal method, and the high theoretical specific capacity and resource richness of Fe2O3 and Mn2O3 are combined with heterostructure and adaptive design to form an electrode with excellent electrochemical performance. Material.
It improves the cycle stability and rate performance of lithium-ion batteries, achieves high capacity, safe working potential and good electrochemical performance, and at the same time, it has rich raw material reserves, low price, and simple and easy to operate.
Smart Images

Figure CN119284968A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion battery electrode materials, and specifically relates to a porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium ion batteries and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are gradually gaining attention in the energy storage industry due to their environmental friendliness, long life, no memory effect, and high energy density. However, the current commercial graphite anodes have disadvantages such as low theoretical specific capacity, unsafe embedding potential, slow electrochemical kinetics, and poor rate performance, which cannot meet the growing energy demand of the energy storage industry, especially their working potential (0.1 V vs. Li + / Li) may lead to "dead" lithium and lithium dendrites, which in turn lead to rapid capacity decay and greatly reduced safety. Therefore, it is of great significance to develop new lithium-ion battery anodes with high specific capacity, safe working potential and rate performance. Metal oxides such as Fe2O3, Mn2O3, Cr2O3, etc. have become alternative options due to their high theoretical capacity and abundant resources. However, these materials have the disadvantages of large volume expansion, low inherent conductivity, irreversible structural collapse, uncontrollable particle aggregation, slow electrochemical reaction kinetics, resulting in poor rate performance and cycle stability, which limits the improvement of the cycle life of lithium-ion batteries. Among the many strategies to solve the above problems, special morphology design and structural optimization are the most effective solutions.
[0003] Among various morphologies, porous core-shell structures are widely used to buffer the volume change of materials during battery cycling because of their adaptive characteristics to the tension caused by structural changes during battery cycling. On the other hand, heterogeneous structures can effectively exert the synergistic effect between the two materials to enable the materials to obtain better electrochemical performance. Then the combination of the two strategies should be able to obtain materials that can buffer volume changes and have good electrochemical properties. In addition, the theoretical specific capacity of Fe2O3 is as high as 1007 mAh g -1 , Mn2O3 has a higher theoretical specific capacity (1018 mAhg -1 ), in addition, the two materials are very abundant in nature and cheap. More importantly, the redox potentials of the two materials are intertwined, which provides a buffer matrix for each other. Summary of the invention
[0004] The technical problem to be solved by the present invention is to propose a porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries and a preparation method thereof in response to the above-mentioned prior art. The raw materials for the preparation of the material are abundant in reserves and low in price, and the production method is simple and safe. The prepared porous Fe2O3@Mn2O3 core-shell cubic structure electrode material has excellent electrochemical properties and can be used as a negative electrode material for lithium-ion batteries.
[0005] A method for preparing a porous Fe2O3@Mn2O3 core-shell cubic structure material for a lithium-ion battery, the preparation method comprising the following steps: S1. Add (CH2OH)2 to deionized water and stir to obtain an ethylene glycol aqueous solution; S2. Add Fe(NO3)3·9H2O, MnSO4·H2O, CH4N2O into ethylene glycol aqueous solution and stir evenly; S3. The mixed solution is poured into a micro high temperature autoclave and heated with stirring, and a hydrothermal reaction is performed; S4. The mixed solution was taken out and cooled naturally to room temperature, and the resulting precipitate was washed several times by centrifugation with ethanol and deionized water, and then dried to obtain a precursor powder; S5. Finally, the precursor powder is sintered in an air atmosphere to obtain a porous Fe2O3@Mn2O3 core-shell cubic structure electrode material.
[0006] The volume ratio of (CH2OH)2 and deionized water in S1 is 1:1; The molar ratio of Fe(NO3)3·9H2O to MnSO4·H2O in the S2 is 1:1; the molar ratio of Fe(NO3)3·9H2O to CH4N2O is 1:10; The hydrothermal reaction temperature in S3 is 140-160° C., for example, 140, 150, 160° C.; the hydrothermal reaction time is 10 h, the stirring speed is 600 rpm, and the pressure is 3-4 MPa, for example, 3, 4 MPa; The sintering temperature in S5 is 800°C, the temperature is kept for 4 h, and the heating rate is 20°C min -1 ; In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: The invention uses a one-step hydrothermal method to produce a porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium ion batteries. The material has a particle size of 5-6 um and mesopores of 100-150 nm. The unique structure and mesopores increase the contact area between the electrode material and the electrolyte, shorten the diffusion distance of ions and electrons, and provide enough free space to adapt to the volume change of the electrode material, thereby improving the cycle stability of the material to a certain extent. When used as a negative electrode active material for lithium ion batteries, the porous Fe2O3@Mn2O3 material exhibits the characteristics of high capacity, good rate performance and good cycle stability. Fe2O3 and Mn2O3 serve as each other's matrix and are uniformly dispersed in each other. The two materials are in direct contact in a micro region, and the electrochemical properties of the material and the synergistic effect between the two materials can be fully exerted. Secondly, the raw materials used in the invention are abundant in reserves, low in price, and the process is simple and easy to operate. The porous Fe2O3@Mn2O3 core-shell cubic structure electrode material precursor can be obtained after solid-phase sintering in a dry and air atmosphere to obtain the porous Fe2O3@Mn2O3 core-shell cubic structure electrode material.
[0007] The invention has strong feasibility, is easy to scale up, conforms to the characteristics of green chemistry, and is conducive to market promotion. The method for producing porous Fe2O3@Mn2O3 core-shell cubic structure electrode material is simple and easy to operate, the production raw material reserves are abundant, the price is low, and the prepared material has high purity and uniform structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and should not be regarded as limiting the scope.
[0009] Image Captions Figure 1 Schematic diagram of the preparation process of a porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries; Figure 2 This is the XRD diagram of the porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries in Example 1; Figure 3 (a) is the SEM of porous Fe2O3@Mn2O3 core-shell cubic structure material; Figure 3 (b) is the EDS result of Fe element; Figure 3 (c) is the EDS result of Mn element; Figure 3 (d) is the EDS result of O element; Figure 4 This is a battery rate diagram of the porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries in Example 1; Figure 5This is a long cycle performance diagram of the porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries in Example 1; Figure 6 This is a long cycle performance diagram of the porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries in Example 1 and Comparative Examples 1, 2, and 3. DETAILED DESCRIPTION
[0010] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all the embodiments.
[0011] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, those skilled in the art can select within a suitable range through the description of the text.
[0012] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0013] Example 1 A method for preparing a porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries comprises the following steps: (1) Mix 25 ml of ethylene glycol solution and 25 ml of deionized water in a ratio of 1:1 and heat and stir at 45°C for 2 min. (2) Dissolve 4 mmol Fe(NO3)3·9H2O, 4 mmol MnSO2·H2O, and 40 mmol CO(NH2)2 in The ethylene glycol aqueous solution prepared in step (1) was stirred in a water bath at 45°C for 30 min.
[0014] (3) After stirring evenly, the mixed solution was poured into a small stainless steel pressure reactor and heated and stirred. The hydrothermal reaction temperature was 150°C, the hydrothermal time was 10 h, the stirring speed was 600 rpm, and the pressure was 3 MPa.
[0015] (4) After the reaction is completed, the reaction product of the above reaction is taken out, and after cooling to room temperature, the obtained precipitate is centrifuged and washed several times with ethanol and deionized water, and then dried in an oven at 70° C. in an air atmosphere to obtain a precursor powder; (5) Finally, the precursor was heated in air at 20 °C min -1The porous Fe2O3@Mn2O3 core-shell cubic structure electrode material can be obtained by heating the temperature to 800℃ and keeping it for 4 h.
[0016] Taking the porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries as an example, the experimental flow chart is as follows: Figure 1 Its structure was determined by X-ray diffractometer. Figure 2 The X-ray diffraction pattern (XRD) shown in the figure shows that the porous Fe2O3@Mn2O3 core-shell cubic structure electrode material is consistent with the standard samples of Fe2O3 with the card number JCPDS: 24-0072 and Mn2O3 with the card number JCPDS: 31-0825, indicating that the prepared porous Fe2O3@Mn2O3 core-shell cubic structure electrode material is indeed a composite of two pure substances. Figure 3 The SEM and EDS images shown indicate that the produced porous Fe2O3@Mn2O3 core-shell cubic structure electrode material has good structural stability.
[0017] The porous Fe2O3@Mn2O3 core-shell cubic structure electrode material obtained in this embodiment is used as a negative electrode active material for lithium-ion batteries as follows: The production process of the negative electrode sheet uses porous Fe2O3@Mn2O3 core-shell cubic structure electrode material as the active material, acetylene black as the conductive agent, 4% polyvinylidene fluoride (PVDF) dissolved in an appropriate amount of N-methylpyrrolidone as the binder, and the mass ratio of active material, acetylene black, and carboxymethyl cellulose is 70:20:10; after the active material and acetylene black are fully mixed in proportion, a certain amount of N-methylpyrrolidone is added, and the mixed solution is evenly ground, and the resulting mixed solution is coated on the copper foil. The coated electrode sheet is placed in an oven at 70°C for 24 hours and then taken out to be made into an electrode sheet with a diameter of 14 mm for standby use. 1M lithium hexafluorophosphate (LiPF6) is dissolved in ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1 as the electrolyte, lithium sheet as the negative electrode, Celgard 2500 microporous polypropylene membrane as the separator, and CR2023 stainless steel as the battery shell to assemble into a button-type lithium-ion battery. The remaining steps of the lithium-ion battery production method are the same as the usual production method.
[0018] Attached Figure 4 The rate performance of the porous Fe2O3@Mn2O3 core-shell cubic structure electrode material at different current densities is shown. -1 , 200 mA g -1 , 500 mA g -1 , 1000 mA g -1and 2000 mA g -1 At current densities of 2.5 and 1.3 GHz, the discharge capacity of the porous Fe2O3@Mn2O3 core-shell cubic structure electrode material can reach 1073.4 mAh g -1 、857.9 mAhg -1 、722.2 mAh g -1 、606.2 mAh g -1 , 426.9 mAh g -1 The material has excellent rate performance, and can -1 After charge and discharge cycles at different current densities, when the current density returns to 500 mA g -1 The capacity can be restored to 730.5 mAh g -1 When the current density returns to 100 mA g -1 The capacity can be restored to 997.5 mAh g -1 , indicating that the material has good structural stability.
[0019] From the attached Figure 5 It can be seen that the cycling stability of the material is also very outstanding. -1 At a current density of 1.5 Å, the discharge capacity can still maintain 77.6% after 300 cycles. The above performance shows that the porous Fe2O3@Mn2O3 core-shell cubic structure electrode material has very excellent electrochemical properties and is a potential negative electrode material for lithium-ion batteries.
[0020] Comparative Example 1 The only difference between this comparative example and Example 1 is that the hydrothermal reaction temperature is 140° C., and the other conditions and parameters are exactly the same as those in Example 1.
[0021] Comparative Example 2 The only difference between this comparative example and Example 1 is that the hydrothermal reaction temperature is 160° C., and the other conditions and parameters are exactly the same as those in Example 1.
[0022] Comparative Example 3 The only difference between this comparative example and Example 1 is that the hydrothermal reaction pressure is 4 MPa, and the other conditions and parameters are exactly the same as those in Example 1.
[0023] Results Analysis Table 1 is the results of the embodiments of the present invention and the comparative examples.
[0024] From Table 1 and Figure 6It can be seen from Example 1 that the battery made of the porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium ion battery prepared by the method of the present invention has a high discharge capacity and capacity retention rate. -1 At a current density of 1.3 mAh g, the discharge capacity of Example 1 is the highest, which is 760.3 mAh g -1 The capacity retention rate after 300 cycles is 77.6%, which is the best performance. The second is comparative example 1, with a discharge capacity of 729.2 and a capacity retention rate of 65.2% after 300 cycles. The discharge capacity of comparative example 3 is the lowest, which is 562.1 mAh g -1 , the capacity retention rate is 31.4% after 300 cycles, while the performance of Comparative Example 2 is between Comparative Example 1 and Comparative Example 3, with a higher discharge capacity and a lower capacity retention rate.
[0025] The above contents are further detailed descriptions of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Without departing from the concept of the present invention, it is also possible to make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be deemed to belong to the protection scope of the present invention.
Claims
1. A method for preparing a porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries, characterized in that: The following steps are involved: S1. Add (CH2OH)2 to deionized water and stir to obtain an ethylene glycol aqueous solution; S2. Add Fe(NO3)3·9H2O, MnSO4·H2O, CH4N2O into ethylene glycol aqueous solution and stir evenly; S3. The mixed solution is poured into a micro high temperature autoclave and heated with stirring, and a hydrothermal reaction is performed; S4. The mixed solution was taken out and cooled naturally to room temperature, and the resulting precipitate was washed several times by centrifugation with ethanol and deionized water, and then dried to obtain a precursor powder; S5. Finally, the precursor powder is sintered in an air atmosphere to obtain a porous Fe2O3@Mn2O3 core-shell cubic structure electrode material.
2. The method for preparing a porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium ion batteries according to claim 1, characterized in that: The volume ratio of (CH2OH)2 and deionized water in S1 is 1:
1.
3. The method for preparing a porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries according to claim 1, characterized in that: The molar ratio of Fe(NO3)3·9H2O to MnSO4·H2O in the S2 is 1:1; the molar ratio of Fe(NO3)3·9H2O to CH4N2O is 1:
10.
4. The method for preparing a porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries according to claim 1, characterized in that: The hydrothermal reaction temperature in S3 is 140-160° C., the hydrothermal reaction time is 10 h, the stirring speed is 600 rpm, and the pressure is 3-4 MPa.
5. The method for preparing a porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries according to claim 1, characterized in that: The sintering temperature in S5 is 800°C, the temperature is kept for 4 h, and the heating rate is 20°C min -1 .
6. A porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries, characterized in that: The preparation method according to claim 1 is adopted.
7. The porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries according to claim 6, characterized in that: The porous Fe2O3@Mn2O3 core-shell cubic structure material has a particle size of 5-6 um and mesopores of 100-150 nm.
8. The porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries according to claim 6, characterized in that: at 100 mA g -1 , 200 mA g -1 , 500 mA g -1 , 1000 mA g -1 and 2000 mA g -1 At a current density of 1.34 Å, the discharge specific capacities of the porous Fe2O3@Mn2O3 core-shell cubic structure electrode materials are 1073.4 mAh g -1 、857.9 mAhg -1 、722.2 mAh g -1 、606.2 mAh g -1 , 426.9 mAh g -1 ; After 100 - 2000 mA g -1 After charge and discharge cycles at different current densities, when the current density returns to 500 mA g -1 When the capacity is restored to 730.5 mAh g -1 When the current density returns to 100 mA g -1 The capacity is restored to 997.5 mAh g -1 ; at 1000 mA g -1 At a current density of , the capacity retention rate after 300 cycles is 77.6%.
Citation Information
Patent Citations
Process for production of active material and electrode, active material, and electrode
CN101127399A
Method for preparing phosphate series lithium ion battery anode material
CN102088080A
Method for preparing nanocomposite of MnO2 / C / Fe2O3 layer-upon-layer structure
CN104851597A
Anode material for lithium-ion battery and preparation method of anode material
CN105489860A
Preparation method of multi-level nano-structure lithium-sulfur battery positive electrode material
CN108242541A